Corynebacterium bovis infection after autologous fat grafting in breast augmentation: a case report - You, Xin; Yao, Yao; Gao, JianHua; Liao, YunJun (Frontiers in Cellular and Infection Microbiology, 2023)
In this report, we present a case study of a rare human bacterium, Corynebacterium bovis, which caused an infection in a patient who had undergone autologous fat-based breast augmentation using cryopreserved fat. This infection occurred during a secondary fat grafting procedure. To identify the bacteria causing the infection, we used high-throughput DNA sequencing technology since this bacterium is seldomly reported in human infections. The patient was successfully treated with intravenous imipenem. We also discuss potential factors that may have contributed to this unusual bacterial infection and propose that DNA sequencing can be a useful tool in cases where standard culture techniques fail to identify the causative agent. Additionally, we highlight the importance of further research on the cryopreservation of fat. In summary, this case highlights the possibility of rare bacterial infections occurring after fat grafting procedures and emphasizes the importance of identifying the causative agent through advanced techniques such as DNA sequencing. Further research is needed to improve our understanding of the risks associated with cryopreservation of fat and to identify ways to prevent these types of infections in the future.